Some Models for Predicting Volume of Populus deltoides - Pandey, Rajiv; Dhall, S. P.; Kanwar, B. S.; Bhardwaj, S. D. (Indian Forester, 1998)
Cross-validation technique is discussed for the validation purpose of models with brief review of the technique in forestry literature. Results of two volume estimation models have been analysed with definition of few terms viz.. apparent error. true error and excess error.